Pengaruh Kreativitas Guru dan Motivasi Belajar Siswa Terhadap Hasil Belajar Siswa Pada Mata Pelajaran Akuntansi Kelas XI di SMKN 1 Jeneponto - Israwati; Muhammad Azis; Sitti Hajerah Hasyim (Asosiasi Dosen Akuntansi Indonesia, 2026)
This study aims to determine the effect of teacher creativity and learning motivation on the learning outcomes of class XI Accounting students at SMKN 1 Jeneponto. The population of this study was 61 students of class XI AKL 1 and XI AKL 2 accounting expertise program at SMKN 1 Jeneponto, while the overall sample population was 61 students taken using saturated sampling techniques. Data collection was carried out using questionnaires and documentation. Data analysis was carried out using descriptive statistical analysis, instrument testing, classical assumption testing and hypothesis testing. The results showed that teacher creativity had a simultaneous effect on student learning outcomes. Learning motivation partially had a significant effect on student learning outcomes. Learning motivation was the most dominant influence on student learning outcomes. Teacher creativity and learning motivation simultaneously had a significant effect on the learning outcomes of class XI accounting expertise program at SMKN 1 Jeneponto. Teacher creativity and learning motivation partially had a significant effect on the learning outcomes of class XI accounting expertise program at SMKN 1 Jeneponto.